2016
DOI: 10.1016/j.rmed.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heated and humidified high flow gases during high-intensity constant-load exercise on severe COPD patients with ventilatory limitation

Abstract: HFNC may improve the exercise performance in severe COPD patients with ventilatory limitation. This effect is associated to an improvement of SaO2 and perceived symptoms at iso-time. In a Pulmonary Rehabilitation program HFNC may allow a given high intensity load to be sustained for a longer time with less symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 16 publications
3
64
0
5
Order By: Relevance
“…In contrast to the results of the present study, Cirio et al . found an increase in endurance time with NHF . In that study, the patients carried out the control test using a Venturi mask relayed to air or oxygen with the aim of providing the same FiO 2 in both conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the results of the present study, Cirio et al . found an increase in endurance time with NHF . In that study, the patients carried out the control test using a Venturi mask relayed to air or oxygen with the aim of providing the same FiO 2 in both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological effects of NHF could help to improve exercise tolerance in those with COPD and requires less technical expertise than NIV. A pilot study showed improvements in endurance, oxygenation and dyspnoea with NHF . However, that study compared NHF with a Venturi mask which is not commonly used in rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Above a flow of 20 L/min, HFNC generates a positive pressure in the upper airways [74], inducing an increase in alveolar ventilation, improvements in gas exchange and a reduction in WOB in patients with COPD [75, 76]. Preliminary reports indicate that HFNC may improve exercise performance, oxygen saturation and perceived symptoms in patients with severe COPD and ventilatory limitation [77]. Whether these preliminary results can also be applied to patients with CVF should be the object of future research.…”
Section: Potential Alternatives and Future Applicationsmentioning
confidence: 99%
“…These mechanisms lead to improved exercise performance with fewer symptoms and better gas exchange [85,88,89], improved lung mechanics [90] with less respiratory muscle load [91] and less work of breathing [86]. Since NIV is used currently as a treatment option in patients with COPD and chronic hypercapnia [92], it seems that NHF could be used instead of NIV in the least tolerant and compliant patients, or in association with NIV, to reduce mask-related side-effects [89].…”
Section: No Benefitmentioning
confidence: 99%